Growth Performance And Nutritional Value Of Scenedesmus Obliquus Cultured In Different Concentrations Of Sweetmeat Factory Waste Media - Toyub, MA; Miah, MI; Habib, MAB; Rahman, MM (Bangladesh Journal of Animal Science, 2012)
The growth performance of Scenedesmus obliquus was studied in the laboratory in different concentration of sweetmeat factory waste media (SFWM). Four different concentrations viz. 1.5, 2.0, 2.5 and 3.0% of SFWM and Bold basal medium (BBM) as control was used with three replications for a period of three months. Each trial was done for a period of 14 days in the laboratory. The initial density of Scenedesmus obliquus was 2.1×105 cell/ml which attained a maximum density of 136.30×105 cell/ml in BBM followed by 97.05, 83.21, 65.19 and 51.21 (×105 cell/ml) in 2.5, 0.3, 2.0 and 1.5 % SFWM respectively on the 10th day of culture. Highest chlorophyll a content was also observed on the 10th day of culture with value of 6.14 and 5.52 mg/l in BBM and SFWM, respectively. The specific growth rate (SGR, m/day) and total biomass were significantly (P<0.05) higher in BBM than all other treatments. The overall growth performance of the alga Scenedesmus obliquus was significantly (P<0.05) higher in 2.5% SFWM than other concentrations of SFWM. The cultured microalgae were found nutritionally rich. During the whole culture period the pH range was 7.03 to 8.05. The other physico-chemical parameters of the culture media were found within the suitable range of the microalgae culture. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9874 BJAS 2008; 37(1): 86-93